DETERMINAN YANG MEMPENGARUHI IBU HAMIL UNTUK PEMERIKSAAN HIV DI WILAYAH KERJA PUSKESMAS RAWANG PASAR IV KABUPATEN ASAHAN - Banjarnahor, Ujur Anwar; J.El-Matury, Herlina; Sitorus, Friska Ernita (Jurnal Kajian Kesehatan Masyarakat, 2024)
The HIV virus can be transmitted from an HIV-infected mother to her child during pregnancy, childbirth and breastfeeding. Transmission from momy to son also tends to increase as the number of HIV positive women increases. The study purpose the determinants is affect pregnant women for HIV testing at the Rawang Pasar IV Health Center in Asahan District in 2023, with a survey research type using a cross sectional design. The population in this study were pregnant women in the Worked Area of the Rawang Pasar IV Community Health Center with a total of 138 people. The sampled technique used is purposive sampled. Data collection was carried out by interviewing used a questionnaire. Bivariately with the Chi-Sqare test at 95% confidence level, α=5%. The results of the analysis showed that there was a relationship between the age of pregnant women and the participation of pregnant women for HIV testing, occupation, knowledge, attitude with the participation of pregnant women for HIV testing. For the Asahan District Health Office to increase the role of midwives and private practice doctors to implement the PMTCT program so that they are able to reach more pregnant women, including working pregnant women who do not have time to come during the opened hours of the Puskesmas service